1998
DOI: 10.1136/jnnp.65.3.308
|View full text |Cite
|
Sign up to set email alerts
|

Dural arteriovenous fistulas as a cause of intracranial hypertension due to impairment of cranial venous outflow

Abstract: Objectives-A retrospective study was carried out on 13 patients with intracranial dural arteriovenous fistulas (DAVFs) who presented with isolated or associated signs of intracranial hypertension. Methods-Nine patients presented with symptoms of intracranial hypertension at the time of diagnosis. Ocular fundoscopy available in 12 patients showed bilateral papilloedema in eight and optic disk atrophy in four. Clinical evolution was particularly noticeable in five patients because of chronic (two patients) or ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
105
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(111 citation statements)
references
References 31 publications
3
105
0
3
Order By: Relevance
“…This phenomenon was already described by Lasjaunias et al 2 and further elaborated by others. [23][24][25] As described by Cognard et al, all patients with a dementia syndrome in this series demonstrated retrograde flow in the draining sinus (Cognard type II), causing the venous hypertensive state. 23 It resulted in death or severe disability in all 4 cases.…”
Section: Discussionmentioning
confidence: 82%
“…This phenomenon was already described by Lasjaunias et al 2 and further elaborated by others. [23][24][25] As described by Cognard et al, all patients with a dementia syndrome in this series demonstrated retrograde flow in the draining sinus (Cognard type II), causing the venous hypertensive state. 23 It resulted in death or severe disability in all 4 cases.…”
Section: Discussionmentioning
confidence: 82%
“…10) The pathogenesis of dural AVF remains controversial, 5,17) but may involve abnormal embryonic development of the vasa vasorum of the sinus or congenital anomalies of the dural vessels. 11) On the other hand, acquired dural AVFs are widely reported to grow secondary to sinus thrombosis, 2,12) trauma (including iatrogenic), 18,19) tumor resection, 9,13,20) infection, 3) and other causes.…”
Section: Introductionmentioning
confidence: 99%
“…22,23,27,32,34,35,39 In severe cases, clinical signs or symptoms of increased intracranial pressure may be present. 9 The mode of presentation is also intrinsically linked to DAVF location. 1,6,10,34 Anterior fossa lesions are fed by ethmoidal arteries and frequently drain into the cavernous sinus.…”
Section: Presentationmentioning
confidence: 99%